Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 66. Beitrag. Hymenoptera: Tiphiidae. - Oehlke, Joachim (Contributions to Entomology = Beiträge zur Entomologie, 1967)
The present paper evaluates the Tiphiidae collected by the expedition to Albania by Deutsches Entomologisches Institut. The material totals 21 individuals of 2 species. Of the 7 species of this family that are supposed to exist on the Balkan peninsula, 4 species been found in Albania. All definitions of species that can be made now should be regarded as provisional.